Safety, tolerability, and immunogenicity of a DNA-based vaccine (INO-4700) against Middle East respiratory syndrome coronavirus: phase 2a study in healthy volunteers - Agnes, Joseph T.; Marcus, Sarah A.; Al-Ghraibeh, Sahem S.; Al-Sweedan, Suleimman Ahmad; Kosgei, Josphat; Ogutu, Bernhards; Yang, ShuPing; Walker, Kathleen A.; Orizu, Bonaventure; Broderick, Kate E.; Boyer, Jean; Ramos, Stephanie; et al. (Frontiers in Immunology, 2025)
BackgroundMiddle East respiratory syndrome coronavirus (MERS-CoV) poses an ongoing public health risk with a 36% case-fatality rate and no licensed vaccines. This Phase 2a, randomized, blinded, placebo-controlled, multi-center trial (MERS-201; NCT04588428) evaluated the safety, tolerability, and immunogenicity of INO-4700, a DNA vaccine against the MERS-CoV spike glycoprotein, in healthy adult volunteers.MethodsParticipants received INO-4700 or placebo intradermally followed by electroporation upon enrollment into any one of five active treatment groups, resulting from three-dose levels (0.6 mg, 1 mg, and 2 mg total) during each of two dosing days or four placebo groups. Doses were administered as 1 or 2 concurrent injections to achieve the total dose level at Week 0 and at either Week 4 or 8. Safety endpoints included incidence of treatment-emergent adverse events (TEAEs), their toxicity grading scale, seriousness, and relationship to study treatment and AEs of special interest (AESI). Immunogenicity endpoints included evaluation of humoral and cellular immune responses, assessed pre-dose (Screening and/or Week 0) and at Weeks 6 and 10.ResultsOne hundred and ninety-two participants were randomized across the nine study groups and followed up between June 2021 and January 2023. Treatment with INO-4700 was well-tolerated and had a favorable safety profile with low incidence of TEAEs, which were overall similar between INO-4700 and placebo groups, with most of the TEAEs assessed as Grade 1 or Grade 2, non-serious, and unrelated to treatment. Group E, the highest INO-4700 dose tested (2 mg total), showed greater immune responses compared to other groups, with significantly elevated MERS-CoV receptor-binding domain (RBD) and spike-binding IgG levels, and seroreactivity at Week 10 peaking at 42% and 32%, respectively. Spike-specific T cell responses further contributed to INO-4700 immunogenicity, ranging from 29% in Group C to 50% in Group E.ConclusionsDNA vaccine INO-4700 was well-tolerated in healthy adults across all groups after each dose was administered and elicited humoral and cellular immune responses. These results warrant further evaluation of INO-4700 as a candidate vaccine for MERS-CoV outbreak preparedness and prevention.Clinical Trial Registrationhttps://clinicaltrials.gov, identifier NCT04588428.